Coming Close : Forty Essays on Philip Levine. - L'Esperance, Mari (University of Iowa Press, 2013)
This collection of essays pays tribute to Philip Levine as teacher and mentor. Throughout his fifty-year teaching career, the Pulitzer Prize-winning Levine taught scores of younger poets, many of whom went on to become famous in their own right. These forty essays honor and celebrate one of our most vivid and gifted poets. Whether in Fresno, New York, Boston, Detroit, or any of the other cities where Levine taught, his students benefited from his sharp, humorous honesty in the classroom. In these personal essays, poets spanning a number of generations reveal how t.